Estado nutricional, consumo alimentar e prática de atividade física em adultos no Nordeste Brasileiro - Melo, Andrea Gomes Santana de (2022)
Food and nutrition are healthy for human health. Nutritional deviations base for the treatment of diseases that serve the population The objective of the study was to investigate the nutritional status and lifestyle habits of the adult population. The study is descriptive, cross-sectional, with secondary data collection in the database of the Surveillance System of Risk and Protection Factors for Chronic Diseases by Telephone Survey (Vigitel), from the year 2019. The investigated population were adults over 18 years of age residents in the capitals of northeastern Brazil. as obesity, were overweight, consumption of fruits and vegetables and physical activity. Of the 18.557% men, 65.1% were women and 34.9% were men. Obesity present in all occurrences of weight in older women. The most prevalent overweight in Recife and Salvador and obesity in Recife, Maceió and João Pessoa. The intake of fruits and vegetables was more common in women from Recife and Aracaju, as was the practice of physical activity in the capitals of Salvador and Maceió. In general, women increased the risks, better consumption of food and adherence to physical exercise. Regardless of gender, specific actions to promote the health of each population group are more defined, considering the specificities of each population group.